Merayakan Persahabatan Yang Memerdekakan Refleksi Atas Pandangan Odo Casel Tentang Misteri Kehadiran Karya Keselamatan Dalam Liturgi - Pius Manik (Sekolah Tinggi Widya Sasana, 2020)
Scripture shows that liturgy is the basic reason why GOD saved his people so that God’s chosen people might freely worship God (Ex 4:23) in spirit and truth’ (Jn 4:24). Liturgy becomes a mediator and a moment for the real presence of God’s saving deed. The relationship between God and His/Her people is drawn into a reality in our liturgy. Odo Casel reflects on our relationship with God is not a mere speculative idea but it is an objective reality that happens in our daily life. The Encyclic Mediator Dei emphasizes the Divine aspect of God’s grace in the history of salvation that restored our relationship with God.